A multi-scenario model for empty container repositioning with uncertain demand. (1st January 2014) - Di Francesco, Massimo; Lai, Michela; Zuddas, Paola
This paper investigates the maritime repositioning of empty containers when their demand is uncertain. It involves moving empty containers from import-dominant ports to export-dominant ports in anticipation of future demands. In order to consider demand uncertainty, the problem is addressed by a stochastic programming approach, in which different scenarios are included in a multi-scenario optimisation model and explicitly linked by non-anticipativity conditions. Numerical experiments are carried out to show which benefits are obtained by multi-scenario solutions with respect to their deterministic counterparts, which consider only one point forecast for each uncertain parameter.